Childhood predictors of health limitations in life across 22 countries: a cross-national and cross-sectional analysis - Jason Paltzer; Elizabeth Kwon; Chukwuemeka N. Okafor; R. Noah Padgett; Erik W. Carter; Jessica Benfer; Tyler J. VanderWeele; Byron R. Johnson (BMC Global and Public Health)
Abstract Background Preventing health problems that limit access to age-appropriate opportunities and relationships (health limitations) is critical to promoting human flourishing. Understanding childhood correlates of health limitations provides a vantage point for prevention efforts. Thus, the purpose of this study was to examine the childhood predictors of health limitations across diverse countries. An individual’s self-reported health limitations in adulthood are likely to vary by country, reflecting the influence of diverse sociocultural, economic, religious, and health contexts that characterize each nation. Methods We used data from the Global Flourishing Study, an ongoing 5-year longitudinal study of human flourishing among 202,898 individuals across 22 countries within nationally representative sampling. A Poisson regression model was fit within each country by regressing health problems in adulthood on a set of childhood predictors. We conducted random effects meta-analyses of the regression coefficients to estimate proportions of effects across countries. Our exploratory analysis highlights key early-life experiences, personal attributes, and familial or social circumstances that are associated with self-reported health limitations in adulthood. Results Early predictors of self-reported health limitations in adulthood vary by country, reflecting the influence of diverse sociocultural, economic, religious, and health contexts that characterize each nation. Across all countries, childhood abuse, growing up feeling like an outsider in one’s family, and self-rated health growing up were associated with a greater risk of having a health limitation as an adult. Conclusions We found common factors among countries and some variations in childhood predictors across the 22 countries. This cross-national study illuminates the role of broader societal factors in shaping the relationship between childhood experiences and health limitations as adults.